EFISIENSI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA TEKNOLOGI PENDEDERAN IKAN LELE (Clarias sp) SANGKURIANG - Ristina Siti Sundari; Yudhi Arie Priyanto (Jurnal Teknologi Perikanan dan Kelautan, 2016)
Catfish is now the rising favorite fish to consumpt. This research was conducted to know the influence of application of production factors either simultaneously or partially and also their efficiency hatchery maintenance of Catfish varr Sangkuriang (Clarias sp). The dependent variable was product of benih (Y) and the independent variable were the area of pool (X1), benih (X2), feed (X3) and labour (X4). The other variables descriptively tested were the price of baby catfish (Py) and production factors (Px). The method of research used case study and data gathered purposively from the group of hatchery maintence of catfish varr. Sangkuriang at Sukaratu Village, Sukaratu – Tasikmalaya. The Data were analyzed by using Cobb Douglas production function whereas MPV and Px ratio was counted to find out the level of efficiency within each production factors. The result showed that the analysis of production factors was significant simultaneously. Whereas the analysis of each production factor indicated that either area or labour production factors were non significant partially. But the production factors of benih and feed partially were significant toward production of baby catfish on the hatchery maintenance catfish varr Sangkuriang. The value of Production Elasticity was less than one. It showed that hatchery is in decreasing return to scale. The result of analysis of production factors’s efficiency indicated that area and benih have not already been efficient. So, they were necessary to increase the amount of those production factors. Whereas, production factors of feed and labour were not efficient. So, reducing the amount of application of production factors was necessary to reduce the amount.